Combination of methylene blue with low-power laser in the treatment of experimental (mixed flora) bacterial keratitis (Ukrainian Journal of Ophthalmology, 2026)
The purpose of study was to estimate the effect of methylene blue (MB) with low-power laser irradiation (LPLI) in treatment of bacterial keratitis.Material and methods. Keratitis was made with suspension culture strain of S. aureus and E.coli. Eyes of the animals were divided into 4 groups: 1 — LPLI + MB + Dimethylsulfoxide (DMSO); 2 — LPLI + MB; 3 — ofloxacin; 4 — control without treatment.Results. After 3 days of PDCT when evaluating congestion positive effect was in the first (p = 0.011). In assessing the erosion of the cornea showed a significant difference in the first and second on the seventh day (p = 0.0001 and p = 0.028) with a shift of one day less in the first group. Reduced infiltration and edema after PDCT in the first and second groups were observed on the third day: infiltration — p = 0.0001 and p = 0.001; edema — p = 0.011 and p = 0.006. Reduction or the recovery period of keratitis is marked for 3 days after the application of PDCT compared with antibiotic therapy. DMSO for conducting MB to cells and LPLI decreases term of recover for 1 day compared to MB and LPLI.
Keywords: keratitis; photodynamic chemotherapy; methylene blue